Sericina: revisão e efeitos do biocurativo na cicatrização de feridas na pele - Freitas, Edicleia de (2023)
Sericin is a protein produced by the silkworm, Bombyx mori (Lepidoptera, Bombycidae), and used in the construction of the silk cocoon. A human skin damage treatment application features, with moisturizers, biocompatibility, resources in the adaptation and adaptation processes, and application resources for skin wound treatment. The severity of the severity of the injury can occur in the functional safety of the organ, as in cases of risk. Increasingly effective search for being a constant improvement in the process, and research with the alternative use as an alternative process. In this sense, a curative treatment of sericin, for the treatment of separation, especially for the treatment of clinical treatment, especially for the treatment of scarring, especially for the treatment medium, were studied as research objectives. The review was carried out in PubMed, Science Direct, Lilac, Scopus, Web of Science and Google Scholar databases, using the English descriptors sericin, wound healing and clinical trial without language or publication period limitation. These were randomized clinical trials that used independent studies of skin wound treatments, in wound type, local protein, age and sex of the participants, excluding those who did not meet these criteria. The experimental study was carried out with 40 Wistar rats, randomly divided into four groups: control, with intact skin; burned, received heat induction and not treated; burnt, treated with Aquacel Ag® dressing; and burned, treated with sericin biodressing. The burn was performed in the interscapular region, measuring 1.5 x 1.5 cm in diameter. After 13 years of the experiment, the skin segment that 13 animals were euthanized after routine histological processing, stains by the line and eosinascopic and eosinascopic Masson for microscopic estimates. n the review research, four studies were included, all conducted in Thailand, three treated wounds from donor areas and only one from wounds caused by burns, the studies used previously developed dressings and silver sulfadiazine ointment with sericin addition, respectively. Sericin proved to be efficient in re-epithelialization and, in some studies, silk protein showed better indexes in pain scales, with no reports of adverse reactions or complications. The results of the experiment showed that the sericin biocurative presented similar results to Aquacel Ag® for epidermis thickness and connective tissue quantification, indicating potential in the treatment of burn wounds. Re-epithelialization and neoangiogenesis showed no differences between the treated groups, this finding in the group treated with sericin biodressing as it was influenced by the significant increase in inflammatory infiltrate. It is concluded that there is a lack of clinical trials that use sericin, but that, based on existing studies, the silk biopolymer has good safety and biocompatibility. In the experimental study, the sericin biodressing showed potential application in the healing of burn wounds, verified by the action on the replication of keratinocytes and increase in the connective tissue, requiring additional studies with less deep injuries.